Healthcare service utilization and cost among transition-age youth with autism spectrum disorder and other special healthcare needs. (April 2021) - Ames, Jennifer L; Massolo, Maria L; Davignon, Meghan N; Qian, Yinge; Croen, Lisa A
Youth with autism spectrum disorder often have complex medical needs. Disruptions of healthcare during the transition from pediatric to adult healthcare may put youth with autism spectrum disorder at higher risk of medical emergencies and high medical costs. We conducted a study among transition-age youth (14–25 years old) receiving healthcare at Kaiser Permanente Northern California during 2014–2015. We examined the differences in healthcare utilization and costs among youth with autism spectrum disorder ( n  = 4123), attention deficit and hyperactivity disorder ( n  = 20, 6015), diabetes mellitus ( n  = 2156), and general population controls ( n  = 20, 615). Analyses were also stratified by age and sex. Youth with autism spectrum disorder had the highest utilization of outpatient primary care, mental health, and psychotropic medications and the lowest utilization of obstetrics/gynecology and urgent care. Costs for youth with autism spectrum disorder were higher than those for attention deficit and hyperactivity disorder and general population peers and lower than for diabetes mellitus. Utilization patterns varied by age. Transition-age youth with autism spectrum disorder generally utilize healthcare at higher rates relative to attention deficit and hyperactivity disorder and general population peers but at similar or lower rates than diabetes mellitus peers, indicating this group's complex combination of psychiatric and medical healthcare needs. The relatively high utilization of psychiatric services and low utilization of women's health services in transition-age youth with autism spectrum disorder may have implications for long-term health and warrants additional research. Lay abstract: Youth with autism spectrum disorder often have complex medical needs. Disruptions of healthcare during the transition from pediatric to adult healthcare may put youth with autism spectrum disorder at higher risk of medical emergencies and high medical costs. To understand healthcare utilization during the transition years, we conducted a study among transition-age youth (14–25 years old) receiving healthcare at Kaiser Permanente Northern California during 2014–2015. We examined differences in healthcare utilization and costs among youth with autism spectrum disorder ( n  = 4123), attention deficit and hyperactivity disorder ( n  = 20, 6015), diabetes mellitus ( n  = 2156), and general population controls ( n  = 20, 615). Analyses were also stratified by age and sex. Youth with autism spectrum disorder had the highest utilization of outpatient primary care, mental health, and psychotropic medications and the lowest utilization of obstetrics/gynecology and urgent care. Costs for youth with autism spectrum disorder were higher than those for attention deficit and hyperactivity disorder and general population peers and lower than for diabetes mellitus. Healthcare utilization patterns varied by age. Transition-age youth with autism spectrum disorder generally used healthcare at higher rates relative to attention deficit and hyperactivity disorder and general population peers but at similar or lower rates than diabetes mellitus peers, indicating this group's complex combination of psychiatric and medical healthcare needs. The relatively high utilization of psychiatric services and low utilization of women's health services in transition-age youth with autism spectrum disorder may have implications for long-term health and warrants additional research.